Briefe II (1894-1904) - Graf, Friedrich Wilhelm (Ernst Troeltsch: Kritische Gesamtausgabe, 2015)
Almost 300 letters, postcards, and telegrams from and to Troeltsch reveal the extraordinary productivity of the young Heidelberg Professor of Systematic Theology along with Troeltsch's great determination to develop his own theory of the "modern world." In addition, the letters provide fascinating glimpses into Heidelberg's Protestant and reformed Jewish academic milieu around 1900.